2010
DOI: 10.1007/s00264-010-1174-6
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive versus non-reconstructive treatment of anterior cruciate ligament insufficiency. A retrospective matched-pair long-term follow-up

Abstract: In this retrospective case series 80 patients divided in 40 matched pair groups with an arthroscopically proven ACL insufficiency were followed up for 15 years. One half was reconstructed using an autologous BTB patella graft, the other half was treated by a conservative physiotherapeutic based rehabilitation program. At follow-up the clinical scores (Lysholm, IKDC) showed no significant differences between subjects who had undergone ACL reconstruction and those who had not. Furthermore there was no detectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 25 publications
5
85
3
Order By: Relevance
“…In a prospective study on 63 patients, Wu et al reported similar results from patients with ACL rupture and reconstruction surgery [29]. They also reported a significant deterioration in clinical condition with associated meniscectomy or imperfect control of laxity and They found significant differences in mean IKDC score of the two groups and reported significant differences in the rate of OA in both groups, with a significantly higher rate of OA in conservative treatment [17,25]. Lysholm and Tegener scores showed deterioration of patents' clinical constitution in comparison with results two years after ACL reconstruction.…”
Section: Discussionsupporting
confidence: 57%
“…In a prospective study on 63 patients, Wu et al reported similar results from patients with ACL rupture and reconstruction surgery [29]. They also reported a significant deterioration in clinical condition with associated meniscectomy or imperfect control of laxity and They found significant differences in mean IKDC score of the two groups and reported significant differences in the rate of OA in both groups, with a significantly higher rate of OA in conservative treatment [17,25]. Lysholm and Tegener scores showed deterioration of patents' clinical constitution in comparison with results two years after ACL reconstruction.…”
Section: Discussionsupporting
confidence: 57%
“…However, recent evidence suggests that these procedures do not dramatically improve long-term patient outcomes. [2][3][4][5] Tissue engineering is an alternative approach that seeks to promote functional healing through the design and implantation of constructs containing stem/progenitor cells seeded in a biocompatible scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…ACL dysfunction is considered to be one of the major risk factors of knee OA [1,9,14,15,17,18,29,30]. When the ACL is injured, not only tibio-femoral OA, but also PF-OA progression is seen in long-term follow up [11,23,30].…”
Section: Discussionmentioning
confidence: 99%
“…Even after ACL reconstruction, PF-OA progression has been reported in short to mid-term follow-up periods [10,11]. However, many reports of PF-OA after ACL tear or reconstruction include follow-up data of less than 20 years [10][11][12][13][14][15][16][17][18], and the evaluation of PF-OA in elderly subjects without ACL function has not been well investigated. Moreover, although tibio-femoral OA changes have been well described in previous reports [19][20][21][22], reports on the morphology of PF-OA are rare [5,6,23].…”
Section: Introductionmentioning
confidence: 99%